Development of Coastal Observation System using WEB Camera - MATSUZAKI, Syoichi; MOROHOSHI, Kazunobu; YANAGISHIMA, Shinichi; SUZUKI, Nobuaki; TAKAHASHI, Shigeo; SUZUKI, Kojiro; ARIJI, Ryuichi (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
In order to install the coastal camera observation system economically, a coastal observation system using WEB camera is newly developed. This system covers wide area, controlling the camera' s pan, tilt and zoom periodically. Image processing like time exposure is also applied to observe surf zones. Using this system, we conducted long term continuous observation on tidal flats, river front and surf zone. Web camera is also controlled by many people on real time and sometimes it is difficult to obtain periodical images. In order to complement loss images, a shore line estimation method using ABIC (Akaike' s Bayesian information criterion) is considered. This method estimates the trend of shoreline erosion of Hasaki beach in the autumn of 2006.